Kajian Hukum Terhadap Faktor Penyebab dan Penyelesaian Hukum Anak Sebagai Pelaku Pemerkosaan - Pratama, Praditya Arcy; Alfauzi, Muhamad Luthfi (Universitas Pancasakti Tegal, 2022)
Child crime is an unlawful act committed by a child, in which case the punishment sanction is different from that of an adult offender. This study aims to determine the factors that influence children to commit rape, as well as analyze the judge's considerations in deciding and prosecuting children as perpetrators of criminal acts through studies in the judge's decision regarding children facing the law Number X / Pid.Sus-Anak / 2021 / PN Bgl. in the future. The approach method used is normative juridical because in the specificification of the research used is descriptive anasisis that describes the applicable laws and regulations. The data source that the secondary data uses. The analytical method used by qualitative research focuses on the process and meaning of the results. The main factor in a child committing such a criminal act of rape is the lack of attention and insight from parents and the environment. This is also due to internal and external factors. Nevertheless, the judge in giving the verdict is appropriate and with all considerations that exist for the survival of the child in the future.